Analisis Kepuasan Konsumen Terhadap Pelayanan Bengkel Menggunakan Metode Algoritma C4.5 - Ridho Hayati Alawiah; S Saifullah; Irfan Sudahri Damanik (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Consumer satisfaction is one thing that is very important is assessing the level of service provided by the workshop to its consumers. The purpose of this study was to determine the quality of serviceto consumer satisfaction Zul Keluarga jaya workshop Pematangsiantar in terms of reliability, Responsiveness, Assurance, Emphaty, Tangibles to consumers Zul Keluarga Jaya workshop Pematangsiantar. In the Zul keluarga Jaya workshop Pematangsiantar the five aspects have not been measured with certainty, so the Zul Keluarga Jaya workshop Pematangsiantar found it difficult to determine which aspects should be improved. By using the C4.5 algorithm, the authors try to measure these five aspects so that a decision tree is formed. After doing a manual calculation, then the proof is done using Rapidminer software. Testing conducted with RapidMiner software using the apply model % performance. From the results of calculation using the C4.5 algorithm produced twelve (12) rule rules of the target to be achieved namely six (6) satisfied decisions and six (6) dissatisfied decisions, and the results of lesting with RapidMiner software resulted in an inspiration rate of 94,00%.